Studies in Southeast Asian Melastoma (Melastomataceae), 4. Clarification of Melastoma crinitum in Southeast Asia and the reinstatement of Melastoma molle - Neo, Louise; Tan, Hugh T.w.; Wong, K.m. (Phytotaxa, 2020)
In the most recent revision of the genus Melastoma Linnaeus (1753: 389) across its entire distributional range, seven species were recognized for Peninsular Malaysia and Singapore (Meyer 2001). Our recent studies in Southeast Asian Melastoma have led us to re-examine some of the species defined in that account, including those recorded for Peninsular Malaysia and Singapore (Wong 2015, Wong 2016, Neo et al. 2017).